(untitled) - Whitmire, Richard (San Francisco, 2014)
On the Rocketship: How Top Charter Schools are Pushing the Envelope examines the rise and expansion of leading charter school network Rocketship, revealing the "secret sauce" that makes a successful program.
Keywords: Charter schools,Điều lệ trường học,Điều lệ trường học,Charter schools; Hoa Kỳ,United States